2020
DOI: 10.22541/au.159493194.42634850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basophil activation test: mechanisms and considerations for use in clinical trials and clinical practice

Abstract: The basophil activation test (BAT) is a functional assay that measures the degree of degranulation following stimulation with allergen or controls by flow cytometry and is directly correlated with histamine release. From the bell-shaped curve resulting from BAT in allergic patients, basophil reactivity (given by %CD63+ basophils) and basophil sensitivity (given by EC50 or similar) are the main outcomes of the test. BAT takes into account all characteristics of IgE and allergen and thus can be more specific tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 81 publications
0
38
0
2
Order By: Relevance
“… 4 , 5 The diagnosis of immediate reactions to AX is based mainly on in vivo and in vitro methods, 6 being drug provocation test the gold standard, although it is risky and not recommended in patients with severe reactions. 2 , 7 , 8 In vitro tests are based on the determination of specific IgE (sIgE), with the commercial ImmunoCAP only detecting 20% of allergic patients, and on the quantification of basophil activation after stimulation with the culprit drug, 9 , 10 showing sensitivity around 50%. Among the factors affecting such low sensitivity could be the fact that correct antigenic determinant and/or conjugates are not incorporated to in vitro tests.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 The diagnosis of immediate reactions to AX is based mainly on in vivo and in vitro methods, 6 being drug provocation test the gold standard, although it is risky and not recommended in patients with severe reactions. 2 , 7 , 8 In vitro tests are based on the determination of specific IgE (sIgE), with the commercial ImmunoCAP only detecting 20% of allergic patients, and on the quantification of basophil activation after stimulation with the culprit drug, 9 , 10 showing sensitivity around 50%. Among the factors affecting such low sensitivity could be the fact that correct antigenic determinant and/or conjugates are not incorporated to in vitro tests.…”
Section: Introductionmentioning
confidence: 99%
“…Using a multiparameter staining approach with three allergen components, we demonstrated that CytoBas enabled detection of sensitization to multiple components of the same allergen (RGP; Lol 4) Basophil staining with recombinant allergen tetramers is possible on fresh whole blood samples (Figures 2 and 3), as well as on cryopreserved PBMC (Figures 5 and 6) enabling more flexibility for transport or batch analysis of clinical samples than is currently possible with the BAT, which requires processing of fresh blood within 24 hrs 56 ; 5) In up to 7% of individuals, basophils do not activate upon FcεRI-mediated stimulation, [57][58][59] and these cannot be evaluated using BAT. As antigen binding occurs irrespective of activation, detect specific sensitization and risk of systemic response, without the need for repeat tests that are currently recommended for, for example, peanut allergy.…”
Section: Discussionmentioning
confidence: 99%
“…2 Moreover, laboratory tests can help physicians evaluate anaphylaxis phenotypes and find causative agents. As shown in Table 3, 25,26,[62][63][64][65][66] inflammatory mediators (histamine, tryptase, chymase, carboxypeptidase A3, and platelet-activating factor) are measured during the acute phase and/or stable condition (at least 24 hours after all signs and symptoms have been resolved) to confirm the diagnosis of anaphylaxis. 67 Meanwhile, the basophil activation test, serum-specific IgE measurement, and skin tests as well as component-resolved diagnostics are used to find causative agents.…”
Section: Clinical Features and Predisposing Factorsmentioning
confidence: 99%
“…Increases in some cases of adult healthy controls Limitations in food-allergy in children Skin tests 25,26 -Useful for evaluation of penicillin allergy, food allergy A safe and non-invasive method for patients with a history of anaphylaxis and mastocytosis False positives: β-blockers and angiotensin-converting enzyme inhibitors False negatives: Hymenoptera hypersensitivity Monoclonal antibody: the specificity and sensitivity are not well-defined. Specific serum IgE 25,26 B cells High sensitivity and specificity in Hymenoptera venomspecific IgE Evaluation of platins-specific IgE in the short-time Evaluation of cross-reactivity with drugs Limitations in food allergies, penicillin allergy Component-resolved diagnostics [63][64][65] -Prediction of allergic reaction severity Have greater specificity in food allergy Capable of detecting the causal agent A useful tool in Hymenoptera allergy Lower sensitivity in food allergy Expensive, labour intense Basophil activation test 25,26,66 Basophils Easily assessed Useful diagnosis and management for β-lactams, muscle relaxants, Hymenoptera venom allergies, fish allergy A true reflection of sensitized mast cells Expensive, labour intense Others 25,26 Serum PAF, serum TNF-α, IL-6, and IL-1β, Prostaglandin D2 and leukotrienes E4 and C4, chymase and carboxypeptidase, mast cell activation test PAF, platelet-activating factor; TNF-α, tumour necrosis factor α; IL, interleukin.…”
Section: Low Sensitivitymentioning
confidence: 99%